Kajian Organologi Pembuatan Gitar Akustik Solid Steel String Model Dreadnought Produksi GuitarUs Klaten - Dwi Setyawan; Kiswanto (Program Studi Pendidikan Musik FBS UNP, 2023)
Purpose: This study aims to describe the process of making a solid steel string Dreadnought acoustic guitar produced by GuitarUs and describe the characteristics of this acoustic guitar based on three aspects of sound, playability and craftsmanship, which later this data can be used as a reference in choosing a good quality steel string acoustic guitar. Method: this research uses qualitative research with a grounded theory approach, namely valid, objective and reliable research results presented by researchers based on a combination of observational data extracted from several GuitarUs luthier partners with observational data obtained from GuitarUs. Results and Discussion: The results of the research obtained are that a good, quality Dreadnought solid steel string acoustic guitar must meet the requirements for the three aspects of sound, playability and craftsmanship, which requirements can be fulfilled if in carrying out the production process, a luthier must apply the knowledge of organology and steel string acoustic guitar acoustics.